2022
DOI: 10.3389/fphys.2022.875583
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Cardiovascular Oscillations at 0.1 Hz During Slow Speech Guided Breathing (OM Chanting) at 0.05 Hz

Abstract: Slow breathing at 0.1 Hz (i.e., 6 cycles per minute, cpm) leads to strong cardiovascular oscillations. However, the impact of breathing below 6 cpm is rarely addressed. We investigated the influence of OM chanting, an ancient Indian mantra, with approx. 3 respiratory cpm (0.05 Hz) on the synchronisation of heart period (RR), respiration (RESP) and systolic blood pressure (SBP). Nine healthy, trained speech practitioners chanted three sequences of five subsequent OM with 2 min pauses in between. Each single OM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
(76 reference statements)
2
3
0
Order By: Relevance
“…2, are in line with the previous studies showing the highest HRV at 6 cpm termed as "resonant" frequency (0.1 Hz) [23], [42]. Increased second harmonic amplitude is observed during slow-paced symmetric breath-hold, which is in line with our pilot study [28], [29], which was subsequently reported by Gerard et al [43]. Highest amplitude of HRV is observed at 6 cpm even for SBH condition, suggesting that it is the coherent frequency even for symmetric breathing with breath-hold.…”
Section: A Hrv During Volitional Breathingsupporting
confidence: 93%
“…2, are in line with the previous studies showing the highest HRV at 6 cpm termed as "resonant" frequency (0.1 Hz) [23], [42]. Increased second harmonic amplitude is observed during slow-paced symmetric breath-hold, which is in line with our pilot study [28], [29], which was subsequently reported by Gerard et al [43]. Highest amplitude of HRV is observed at 6 cpm even for SBH condition, suggesting that it is the coherent frequency even for symmetric breathing with breath-hold.…”
Section: A Hrv During Volitional Breathingsupporting
confidence: 93%
“…Overall, the evidence suggests that meditation is a powerful tool that can have a positive impact on the brain and the immune system (Jamil et al, 2023). Consistent with these observations, it was demonstrated that cerebral blood flow increases during chanting meditation (Khalsa et al, 2009), and repeated chanting of a mantra was associated with increased synchronization of the rhythms of respiration, heart period, and systolic blood pressure (Hotho and Cysarz, 2022).…”
Section: Introductionsupporting
confidence: 55%
“…Among the different types of meditative practices, religious chanting plays a significant role because it has a peculiar religious/spiritual dimension, a dimension that has a significant impact on the state of mind (Dick et al, 2014;Hotho and Cysarz, 2022). Chanting is a meditative practice that is prevalent worldwide and plays a significant role in many traditions, either religious or secular.…”
Section: Religious Chanting a Practice Different From All Othersmentioning
confidence: 99%
“…Overall, the evidence suggests that meditation is a powerful tool that can have a positive impact on the brain and the immune system (Jamil et al 2023). Consistent with these observations, it was demonstrated that cerebral blood flow increases during chanting meditation (Khalsa et al 2009), and repeated chanting of a mantra was associated with increased synchronization of the rhythms of respiration, heart period, and systolic blood pressure (Hotho et al 2022).…”
Section: Introduction: the Brain The Mind And The Immune Systemmentioning
confidence: 62%
“…Among the different types of meditative practices, religious chanting plays a significant role because it has a peculiar religious/spiritual dimension, a dimension that has a significant impact on the state of mind (Dick et al 2014;Hotho et al 2022). Chanting is a meditative practice that is prevalent worldwide and plays a significant role in many traditions, either religious or secular.…”
Section: Religious Chanting a Practice Different From All Othersmentioning
confidence: 99%